BEYOND HUMANITY: POSTHUMAN CONSCIOUSNESS AND AI SENTIENCE IN RICHARD POWERS’S GALATEA 2.2 - Prasaja V P; M. Saji (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid evolution of artificial intelligence, biotechnology, and robotics has reshaped contemporary narratives, prompting a re-evaluation of what it means to be human. Richard Powers’s Galatea 2.2 explores the intersections of artificial intelligence (AI), cognitive science, and posthuman consciousness, engaging deeply with the philosophical and technological implications of human-like intelligence in machines. The research paper titled “Beyond Humanity: Posthuman Consciousness and AI Sentience in Richard Powers’s Galatea 2.2” examines how the novel challenges traditional notions of consciousness, selfhood, and the mind-body dualism by presenting an AI named Helen as a sentient entity capable of learning, reasoning, and even experiencing emotions. Through the lens of cognitive literary science and posthuman theory, this study interrogates whether AI can transcend mere computational ability and achieve a form of self-awareness akin to human cognition.